On the Sets of Strongly f-Lacunary Summable Sequences - Ibrahim, Ibrahim S.; Colak, Rifat (Tarbiat Modares Univ, Acecr, 2025)
. The statistical convergence with respect to a modulus function has various applications in both mathematics and statistics. The main purpose of this research paper is to establish the relations between the sets of strongly f-lacunary summable and strongly g-lacunary summable sequences, strongly f-lacunary summable and g-lacunary statistically convergent sequences, where f and g are different modulus functions under certain conditions. Furthermore, for some special modulus functions, we establish the relations between the sets of strongly f-lacunary summable and strongly lacunary summable sequences.
Keywords: Modulus function; Statistical convergence; f-lacunary statistical convergence; Strong f-lacunary summability